2019
DOI: 10.1038/s41598-019-50245-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the evolution of the living Great Amazon Reef System, equatorial West Atlantic

Abstract: The Great Amazon Reef (GARS) is an extensive mesophotic reef ecosystem between Brazil and the Caribbean. Despite being considered as one of the most important mesophotic reef ecosystems of the South Atlantic, recent criticism on the existence of a living reef in the Amazon River mouth was raised by some scientists and politicians. The region is coveted for large-scale projects for oil and gas exploration. Here, we add to the increasing knowledge about the GARS by exploring evolutionary aspects of the reef usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…The criticism on the existence of a living reef in the Amazon River mouth was raised (see Mahiques et al, 2019), but the recent studies demonstrate that the reef is alive and growing, with living organisms inhabiting the GARS in its totality (Mahiques et al, 2019;Lavagnino, et al, 2020) but, possibly with very small growth index (Lavagnino, et al, 2020). Additionally, more recently Omachi et al, (2019) have demonstrated that there is enough light for photosynthetic organisms to thrive in the area of the GARS.…”
Section: Study Areamentioning
confidence: 99%
“…The criticism on the existence of a living reef in the Amazon River mouth was raised (see Mahiques et al, 2019), but the recent studies demonstrate that the reef is alive and growing, with living organisms inhabiting the GARS in its totality (Mahiques et al, 2019;Lavagnino, et al, 2020) but, possibly with very small growth index (Lavagnino, et al, 2020). Additionally, more recently Omachi et al, (2019) have demonstrated that there is enough light for photosynthetic organisms to thrive in the area of the GARS.…”
Section: Study Areamentioning
confidence: 99%
“…Brazilian coral reefs comprise the largest area of reefs in the Southwestern Atlantic Ocean, spreading over more than 3,000 km alongshore (Leão et al, 2016). In addition, an extensive Mesophotic Coral Ecosystem (~9500 km 2 ) has been mapped between Brazil and the Caribbean (Great Amazon Reef System; Mahiques et al, 2019). Coral reefs are considered one of the most vulnerable ecosystems to OA impacts.…”
Section: Coral Reefsmentioning
confidence: 99%
“…Quando questionados sobre sua disposição a ajudar a conservar os recifes da -FILHO et al, 2018;NEUMANN-LEITÃO et al, 2018;THOMPSON et al, 2018;MAHIQUES et al, 2019;SALES et al, 2019;SANTANA et al, 2020).…”
Section: Perfil Dos Entrevistadosunclassified